Drawing and painting botanicals for artists : how to create beautifully detailed plant and flower illustrations - Kluglein, Karen (Rockport Publishers, 2020)
"Drawing and Painting Botanicals for Artists offers artists at all skill levels a comprehensive survey of drawing and painting mediums and techniques, along with guidance for creating accurate, detailed, and beautiful botanical artworks"--